The Effect of Work Engagement and Work Discipline on Employee Performance at PT XYZ, With Work-Life Balance as A Mediating Variable - Naura Agrenia Amini; Ratri Wahyuningtyas (Indonesian Economic Review, 2026)
Employee performance is a critical factor influencing organizational effectiveness, particularly in the construction industry, where project success depends heavily on workforce productivity and commitment. This study aims to examine the effects of work engagement and work discipline on employee performance through work-life balance as a mediating variable at PT XYZ. A quantitative explanatory research design was employed, involving 235 employees selected through a purposive sampling technique. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that work engagement, and work-life balance each have a positive and significant effect on employee performance. Meanwhile, work discipline was found to have no significant effect on employee performance. Furthermore, work engagement and work discipline significantly influence work-life balance. The mediation analysis demonstrates that work-life balance significantly mediates the relationships between work engagement and employee performance as well as between work discipline and employee performance. These findings highlight the importance of fostering employee engagement, strengthening disciplinary practices, and promoting work-life balance to enhance employee performance and organizational effectiveness in the construction sector.